Nrf2-regulated miR-380-3p Blocks the Translation of Sp3 Protein and Its Mediation of Paraquat-Induced Toxicity in Mouse Neuroblastoma N2a Cells. (31st July 2019) - Cai, Zhipeng; Zheng, Fuli; Ding, Yan; Zhan, Yanting; Gong, Ruijie; Li, Jing; Aschner, Michael; Zhang, Qunwei; Wu, Siying; Li, Huangyuan
Abstract: Laboratorial and epidemiological research has established a relationship between paraquat (PQ) exposure and a risk for Parkinson's disease. Previously, we have investigated the effects of nuclear factor erythroid 2 related factor 2 (Nrf2) and microRNAs in PQ-induced neurotoxicity, addressing the function of miR-380-3p, a microRNA dysregulated by PQ, as well as Nrf2 deficiency. Nrf2 is known to mediate the expression of a variety of genes, including noncoding genes. By chromatin immunoprecipitation, we identified the relationship between Nrf2 and miR-380-3p in transcriptional regulation. qRT-PCR, Western blots, and dual-luciferase reporter gene assay showed that miR-380-3p blocked the translation of the transcription factor specificity protein-3 (Sp3) in the absence of degradation of Sp3 mRNA. Results based on cell counting analysis, annexin v-fluorescein isothiocyanate/propidium iodide double-staining assay, and propidium iodide staining showed that overexpression of miR-380-3p inhibited cell proliferation, increased the apoptotic rate, induced cell cycle arrest, and intensified the toxicity of PQ in mouse neuroblastoma (N2a [Neuro2a]) cells. Knockdown of Sp3 inhibited cell proliferation and eclipsed the alterations induced by miR-380-3p in cell proliferation. Two mediators of apoptosis and cell cycle identified in previous studies as Sp3-regulated, namely cyclin-dependent kinase inhibitor 1 (p21) and calmodulin (CaM), were dysregulated by PQ, but not Sp3 deficiency. In conclusion, Nrf2-regulated miR-380-3p inhibited cell proliferation and enhanced the PQ-induced toxicity in N2a cells potentially by blocking the translation Sp3 mRNA. We conclude that CaM and p21 were involved in PQ-induced toxicity.